Analisis Kesalahan Siswa dalam Menyelesaikan Soal Persamaan Kuadrat Berdasarkan Klasifikasi Kastolan - Rahma Wati; Puguh Darmawan (Universitas Maritim AMNI Semarang, 2024)
This research aims to analyze students' errors in solving quadratic equation questions based on the Kastolan classification with test instrument questions adapted to the cognitive level of Bloom's Taxonomy. The subjects of this research were six students of class IX MTsS Simpang Tanjung Nan IV. The type of research used is descriptive qualitative. Instruments include questions, interview guidelines and documentation. Based on this research, conceptual errors were found with a percentage of 58.3%, procedural errors with a percentage of 33%, and technical errors with a percentage of 25%. The dominant errors found are conceptual errors, the teacher's role is needed in preventing and overcoming these errors.